Thyroid Cancer: Current Molecular Perspectives. (14th March 2010) - Giusti, Francesca; Falchetti, Alberto; Franceschelli, Francesco; Marini, Francesca; Tanini, Annalisa; Brandi, Maria Luisa
Abstract : The thyroid cancer is a rare oncological entity, representing no more than 1% of all human malignant neoplasms. Recently, it has been demonstrated a sharp increase in incidence of differentiated thyroid carcinoma, equally occurring in both sexes. So far, multiple genetic alterations have been identified in differentiated thyroid carcinoma, leading to investigate the clinical utility of genetic studies. In particular, molecular genetic approaches searching for gene mutations in the material collected by fine needle ago-biopsy may have a particular utility in small nodules and in those specimens with an indeterminate cytology. The expansion of knowledge about genetic mutations occurring in different thyroid tumors has characterized recent years, allowing the identification of a correlation between specific mutations and phenotypic characteristics of thyroid cancers, essential for their prognosis. This review will briefly report on the histological features and the new entity represented by thyroid microcarcinoma and will focus on both environmental and genetic aspects associated with the occurrence of thyroid cancer.